2013
DOI: 10.1186/1471-230x-13-9
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus impacts risk of macrovascular invasion in patients undergoing transplantation for hepatocellular carcinoma

Abstract: BackgroundDiabetes mellitus (DM) is identified as a negative prognostic indicator in hepatocellular carcinoma (HCC), though the basis for this is unknown.MethodsThis is a retrospective analysis of a prospectively collected database of 191 HCC patients treated at the University of Rochester Medical Center (URMC) with orthotopic liver transplantation between 1998–2008. Clinical characteristics were compared between patients with and without DM prior to liver transplantation and logistic regression analyses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 33 publications
(38 reference statements)
4
11
0
Order By: Relevance
“…Multivariate analysis also indicated that DM was a significant independent predictor of poor survival, but not of HCC recurrence post-LT. This finding is consistent with previous studies that reported decreased post-operative survival rates in HCC patients with DM[23,24,29-32]. …”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Multivariate analysis also indicated that DM was a significant independent predictor of poor survival, but not of HCC recurrence post-LT. This finding is consistent with previous studies that reported decreased post-operative survival rates in HCC patients with DM[23,24,29-32]. …”
Section: Discussionsupporting
confidence: 93%
“…To our knowledge, only two studies have compared the impact of pre-LT DM on survival and tumor recurrence in HCC patients after LT[23,24]. Connolly et al[23] studied 191 LT-treated HCC patients (12 HBV-related, 104 HCV-related and 81 other HCCs) and determined that the median survival was 78.3 mo for the non-DM patients, but only 31.1 mo for the DM patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations